n-Hexadecane, Petroleum Diesel and Biodiesel Fuels for a Direct Hydrocarbon Phosphoric Acid Fuel Cell - Zhu, Yuanchen (Université d'Ottawa / University of Ottawa, 2015)
The performance of a phosphoric acid fuel cell reactor, (PAFC), with n-hexadecane, C16H34, canola biodiesel, soybean biodiesel and petroleum diesel fuel has been investigated. Fifteen-hour steady-state operation was achieved with each of the diesel fuels. This is the first extensive study reported in the literature in which n-hexadecane is used directly as the fuel. It is also the first study of a fuel cell operated with petroleum diesel fuel. Identification of steady-state conditions (temperature = 190oC, molar ratio of fuel to water = 414) is significant because it demonstrates that stable fuel cell operation is technically feasible when operating a PAFC with diesel fuels. Degradation in fuel cell performance was observed prior to reaching steady-state. The degradation was attributed to a carbonaceous material forming on the surface of the anode. After treating the anode with water the fuel cell performance recovered. However, the fuel cell performance degraded again prior to obtaining another steady-state operation. Several consistent observations suggested that the carbonaceous material formed from the diesel fuels might be a reaction intermediate necessary for steady-state operation. Finally, the experiments indicated that water in the phosphoric acid electrolyte could be used as the water required for the anodic reaction. The water formed at the cathode could provide the replacement water for the electrolyte, thereby eliminating the need to provide a water feed system for the fuel cell.
Keywords: Phosphoric acid fuel cell; Steady state